The reality of the professional development of primary school teachers in the city of Riyadh in light of technological innovations - bin Mubrad, Noura Rashed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the reality of the professional development of primary school teachers in Riyadh, Kingdom of Saudi Arabia. In light of technological developments, the study used the descriptive and analytical approach to achieve the objectives of the study, the researcher also used the Abu Laban's questionnaire (2017) as a tool for the study, consisting of (30) paragraphs, after confirming its validity and consistency, the sample of the study consisted of (200) primary school teachers in Riyadh, and the results concluded that the reality of professional development among primary school teachers in Riyadh in light of technological innovations was of a high degree, with an average of (3.51). There were statistically significant differences at the level of significance (α ≤ 0.05) between the averages of the sample's estimates of the degree of professional development among female teachers due to the years of experience variable, and in favor of those with experience (1-5 years), and statistically significant differences were found at the level of significance (α ≤ 0.05) between the averages of the sample's estimates of the degree of professional development of female teachers attributed to academic qualification, and in favor of holders of a master's degree, and the study came out with a set of recommendations, including the necessity to educate primary school teachers about the importance of professional development, and to provide educational environments rich in technological innovations to contribute to the professional development of female teachers, in addition to holding training courses on technological innovations related to the professional development of female teachers.
Keywords: professional development; technological innovation; teacher